Sources of banks’ productivity growth in a developing economy: efficiency change or technological progress? - Sufian, Fadzlan (Inderscience Publishers, 2010)
This paper examines the sources of total factor productivity in the Thailand banking sector during 1999–2008. We employ the output-oriented Malmquist productivity index first, proposed by Shephard (1970) to isolate efforts to catch up to the frontier (efficiency change (EFFCH)) from shifts in the frontier (technological change (TECHCH)). We also explore main sources of EFFCH: either improvements in management practices (pure technical efficiency change) or optimal size (scale efficiency change). The findings indicate that the majority of the medium banks (MED_BNKS) and large banks have exhibited productivity growth, while the majority of the small and MED_BNKS have experienced productivity regress.